How Job Changes Affect People's Lives~ – Evidence from Subjective Well-Being Data - Adrian Chadi; Clemens Hetschko (British Journal of Industrial Relations, 2021)
Starting a new job is able to boost people's careers, but might come at the expense of other areas of life. To investigate individual implications of job mobility, we analyse the effects of job changes on time-use and indicators of subjective well-being using rich data from a representative German panel survey. We find that job switchers report relatively high levels of life satisfaction, at least for the first time after the job change. There is no such `honeymoon' period for job changes triggered by plant closures. Instead, we find evidence for a harmful impact of involuntary mobility on family life.
Keywords: 330